Perancangan dan Pengembangan Permainan “Super Sigi” Menggunakan Stencyl Sebagai Media Pengenalan Menyikat Gigi - Yusnia Alfi Syahrin; Kodrat Iman Satoto; Kurniawan Teguh Martono (Jurnal Teknologi dan Sistem Komputer, 2015)
To maintain and preserve healthy teeth is very important to prevent damage inflicted due to ignore. The introduction for maintaining and preserving the healthy teeth since early seems necessary because the damage of teeth which allowed too long would be bad for children later. The introduction about healthy teeth care for children also can use the role of technology nowadays like multimedia. Based on those things, there is an idea to design and build a game application for helping that issue. Through this “Super Sigi” game, hopefully become an instrumentality of a healthy teeth care introduction especially of brushing the teeth for children. The “Super Sigi” game is made from Stencyl. Stencyl is a toolkit for creating 2D video games that will run on many different mobile and desktop devices. This game developed by the method of Multimedia Development Life Cycle (MDLC) that consists of concept, design, collecting material, assembly, and distribution. The result of this research is a “Super Sigi” game application that can be a utility for children containing an introduction about how to care the teeth. Based on the black-box testing, the whole function of the menu that is in the game has successfully and run according to each function.